Harnessing Digital Technology for Contextual Learning of Local Social Issues: A Systematic Literature Review - Azahari, Abd Rahman; Haridison, Anyualatha (Jurnal Pendidikan Progresif, 2025)
Harnessing Digital Technology for Contextual Learning of Local Social Issues: A Systematic Literature Review. Objectives: This study explores the use of digital technologies in enhancing contextual learning, focusing on their role in addressing local social issues. The research aims to synthesize current literature to identify trends, technological tools, pedagogical frameworks, challenges, and provide recommendations for optimizing the integration of educational technologies in locally relevant learning environments. Methods: Firstly, to use a systematic literature review (SLR) of 27 peer-reviewed studies from the Scopus database, published between 2016 and 2025. Secondly, by following PRISMA 2020 guidelines, the evaluation identifies trends in digital technologies, such as Virtual Reality (VR), mobile learning platforms, and geolocation tools, across various educational contexts. The review assessed the pedagogical approaches and the challenges faced in utilizing these technologies and their social impact. Results: The results highlight a growing use of digital technologies to address local social issues, with significant applications in environmental sustainability, cultural preservation, and healthcare. At the same time, the review reveals a direct relationship between challenges such as gaps in digital infrastructure, limited digital literacy, and the ineffective use of technology in education. These barriers hinder the full potential of digital tools, despite their effectiveness in place-based learning. The study emphasizes that their contextual relevance and cultural sensitivity heavily influence the effectiveness of digital tools. Conclusion: Digital technologies can significantly enhance contextual learning and engage students in solving local social issues. However, future research should focus on bridging the digital divide, creating culturally relevant tools, and promoting co-design processes with local communities, educators, and policymakers to maximize potential. Collaborative efforts should prioritize sustainable and adaptive digital learning solutions that are contextually grounded and technologically accessible. Keywords: digital technologies, contextual learning, educational technology, social issues, digital literacy.